A NEW APPROACH FOR ACETYLATION OF WOOD: VINYL ACETATE - Özmen, Nilgül; Çetin, Nihat Sami; Birinci, Emre; Narlıoğlu, Nasır (The 1st International Symposium on Environment and Forestry, Trabzon, Turkey, 1540-1551, 2010)
he chemical modification of wood has been the subject of research for many decades. The most favoured modification reaction involves the acetylation of wood with acetic anhydride. Reacted acetate provides dimensional stability by bulking the cell wall polymers and reduces further swelling when the woods come into contact with water. In addition that chemical modification also provides biological resistance. With acetylation, it is possible to extent at least twice or three times service life of wood as compared to control one. Acetylation of wood with acetic anhydride is not subject only academic studies, it is also became commercial process since 2003. In Turkey, the study of acetylation of wood with acetic anhydride is limited with academic work. There are two main obstacles commercialization of acetylation in Turkey. One of them is the cost of acetic anhydride, the other is that acetic anhydride is the restricted chemical. The purchase and the stock of acetic anhydride are requiring special permission from Health Ministry because of its use for the synthesis of heroin by the diacetylation of morphine. The purpose of this study is to show the new methods for acetylation of wood. Scots pine (Pinus sylvestris) sapwood was successfully acetylated by the new transesterification reaction with vinyl acetate. Under identical conditions, Scots pine sapwood was also modified with acetic anhydride to compare with the new technique. The results of acetylated wood with acetic anhydride and vinyl acetate were compared, and characterized by Infrared (FTIR) and 13C CP MAS NMR analysis.
Keywords: Acetylation, Acetic anhydride, Vinyl acetate, Scots pine, Chemical modification.